2018
DOI: 10.1016/j.breast.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Induced Protein (PIP) is a potential biomarker for early stage and malignant breast cancer

Abstract: PIP mRNA is significantly downregulated in early stage BC compared to normal breast tissue. Consequently, low PIP mRNA expression in BC tissues could potentially be used as a tissue based biomarker to assist pathologists in confirmation of early stage BC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…PCA readily separated the groups ( Figure 3 C), and a total of 178 proteins was found to be significantly regulated ( Figure 3 B, Table S6 ). Among these, known biomarkers for MB (FSTL5 [ 31 ]), and other tumor types such as neuroendocrine tumors (ENO2 [ 32 ], FMOD [ 33 ], ART3 [ 34 ], COL6A3 [ 35 ]) and PIP [ 36 ], were found to be significantly up-regulated ( Figure 3 B, dark green). A total of 55 regulated proteins were found to be associated with the gene ontology term “leukocyte mediated immunity [2443]” and/or “defense response [6952]”, ( Figure 3 B, brown), most of them characteristic for myeloid cells such as macrophages and strongly indicating an active involvement of immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…PCA readily separated the groups ( Figure 3 C), and a total of 178 proteins was found to be significantly regulated ( Figure 3 B, Table S6 ). Among these, known biomarkers for MB (FSTL5 [ 31 ]), and other tumor types such as neuroendocrine tumors (ENO2 [ 32 ], FMOD [ 33 ], ART3 [ 34 ], COL6A3 [ 35 ]) and PIP [ 36 ], were found to be significantly up-regulated ( Figure 3 B, dark green). A total of 55 regulated proteins were found to be associated with the gene ontology term “leukocyte mediated immunity [2443]” and/or “defense response [6952]”, ( Figure 3 B, brown), most of them characteristic for myeloid cells such as macrophages and strongly indicating an active involvement of immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…In early studies, PIP was shown to be absent in normal breast epithelium, whereas in breast cancers PIP is frequently expressed [ 81 , 82 ]. Others have shown that PIP is frequently present in uninvolved breast tissue [ 84 ]. However, since highly increased levels of PIP have been detected in the peripheral plasma from patients with primary and metastatic breast cancer in comparison to normal subjects, its significance as a potential serum marker in breast cancer is promising [ 51 , 82 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding (Vanneste & Naderi, ) that PIP silencing led to a marked reduction in cell adhesion allowed us to interpret PIP silencing could promote migration and invasion in OSCC cells. In addition, Gangadharan et al () similarly observed considerable downregulation of PIP transcription in cancer samples compared with normal breast tissue. We also found PIP expression in OSCC tissue is lower than normal tissue.…”
Section: Discussionmentioning
confidence: 95%
“…PIP has also been shown to belong to a group of salivary proteins, whose profusion is reduced in the presence of oral bleeding (Fleissig et al, ; Haigh et al, ). PIP has also been reported to associate with secretory lesions and is related to atypical and benign precursors (Asirvatham, Falcone, & Kleer, ; Gangadharan et al, ; Gown, Fulton, & Kandalaft, ). In our study, PIP was found to regulate cell proliferation, migration, and invasion of OSCC cells.…”
Section: Discussionmentioning
confidence: 99%